(untitled) (Prithvi Journal of Research and Innovation, 2022)
Dispute settlement provisions are crucial segments of the securities law for each and every jurisdiction as recognized within core objectives of the securities regulation even by International Organization of the Securities Commissions. This article deals mainly with the questions on how far the dispute settlement provisions in Nepali securities law are adequate to redress and compensate the investors for actual losses resulting from market malpractices. Employing doctrinal legal research followed by in-depth key informant interview with the regulatory representatives, experts and market participants to conduct the study, it is based on descriptive, analytical and interpretative in research design. Drawing upon the analysis of the existing grievances handling mechanism and securities dispute settlement practices, the author concludes that law on securities dispute settlement regime is quite scattered and it seems urgent to have a consolidated approach to bring them at one place within a separate regulation. The study recommends the concerned authorities to restructure the securities dispute settlement regime by means of amendment of the existing securities law to provide a Securities Dispute Settlement Committee under the aegis of the regulator Securities Board of Nepal, which could function as a first-tier quasi-judicial body to look and decide over all kinds of securities disputes. Likewise, the concerned authorities are recommended to pass a separate legislation to establish and form an independent Securities Market Dispute Settlement Tribunal having its jurisdiction to hear an appeal against the decision of the proposed Dispute Settlement Committee under the Securities Board of Nepal.